Egalitarianism: psychological and socio-ecological foundations. (April 2020) - Sheehy-Skeffington, Jennifer; Thomsen, Lotte
Highlights: Societal politics and ideology are undergirded by basic relational strategies rooted in dilemmas of resource distribution. Core representations and motives for equality and hierarchy emerge in infancy. Individual differences in egalitarian strategies manifest in infancy, stabilize in adolescence, and are partly heritable. The extent, consensuality, and predictive power of egalitarianism depend on societal context. A multi-level approach is needed to account for both the biological and socio-ecological foundations of egalitarianism. Abstract : Individual differences in social and political attitudes have their roots in evolved motives for basic kinds of social relationships. Egalitarianism is the preference for the application of the one of these relational models-equality—over that of another—dominance—to the context of societal intergroup relations. We present recent research on the origins of egalitarianism in terms of universal social cognitive mechanisms (activated as early as infancy), systematic (partly heritable) individual differences, and the affordances and constraints of one's immediate and macro-structural context. Just as the psychological impact of socioeconomic conditions depends on the mind being equipped to perceive and navigate them, so the expression of the evolved underpinnings of inequality concerns depends critically on social and societal experiences.